Perspektif Ekonomi Islam pada Jual Beli Online yang Dilakukan oleh Dosen Wanita - Achmad Fuad, Raden; Cahyono, Hendry (Universitas Negeri Surabaya, 2020)
This research wanted to discuss about buying and selling transactions conducted by female lecturers or practically housewives who also work as professors and want to learn how to manage women conducting online trading transactions based on the perspective of Islamic economics. This research method uses descriptive qualitative research methods. The participants of this study discussed three people. The technique of collecting data is by in-depth interviews with the help of key informants. The results of this study suggest the process of buying and selling online transactions conducted by female lecturers coupled with a myriad of housewife activities and activities as teaching staff on campus. As a whole, it can be concluded that the informants stated that the contract made by a number of them doing transactions in buying and selling is murobahah contract.